Grey Wolf based control for speed ripple reduction at low speed operation of PMSM drives - Djerioui, Ali; Houari, Azeddine; Ait-Ahmed, Mourad; Benkhoris, MOHAMED-FOUAD; Chouder, Aissa (Université de M'sila, 2018)
Speed ripple at lowspeed-high torque operation of PermanentMagnet SynchronousMachine (PMSM) drives is considered as one of the major issues to be treated. The presented work proposes an efficient PMSMspeed controller based on Grey Wolf (GW) algorithm to ensure a high-performance control for speed ripple reduction at low speed operation. The main idea of the proposed control algorithm is to propose a specific objective function in order to incorporate the advantage of fast optimization process of the GW optimizer. The role of GW optimizer is to find the optimal input controls that satisfy the speed tracking requirements. The synthesis methodology of the proposed control algorithm is detailed and the feasibility and performances of the proposed speed controller is confirmed by simulation and experimental results. The GW algorithm is a model-free controller and the parameters of its objective function are easy to be tuned. The GWcontroller is compared to PI one on real test bench. Then, the superiority of the first algorithm is highlighted.